Immediate continuous positive airway pressure (CPAP) therapy after sleeve gastrectomy - Asem A. Hewidy (Egyptian Journal of Chest Disease and Tuberculosis, 2016)
Noninvasive continuous positive airway pressure ventilation may improve postoperative oxygenation, lung functions and reduce postoperative complications in morbidly obese patients undergoing sleeve gastrectomy. Aim: Evaluation of the effect of immediate postoperative CPAP therapy after sleeve gastrectomy in improving oxygenation, pulmonary functions values, reducing atelectasis and reducing postoperative pulmonary complications. Patients and methods: Single blind randomized clinical trial, was conducted in Gastroenterology Centre and Chest Department, Mansoura University Hospitals during the period from 2013 to 2015 on 46 morbidly obese patients after sleeve gastrectomy. Patients were divided into two groups; group (A) immediately placed on CPAP (8–12 cm H2O) for at least 8 h and group (B) control group, received oxygen support 4–6 L per minute via nasal catheter. The primary end points of the study were CXR, spirometric pulmonary function (FEV1, FVC, FEV1/FVC) and O2 tension and saturation measured 24 h postoperatively and the secondary endpoints were postoperative pulmonary complications during the first 2 weeks. Results: As regards FEV1 and FVC, there was a high statistically significant difference between both groups after treatment and there was a statistically significant increase in group (A) after treatment versus before treatment. As regards oxygen tension and saturation there were high statistically significant differences between both groups after treatment. There was a statistically significant decrease in atelectasis in group (A). There were statistically significant differences between both groups as regards postoperative respiratory failure and persistent atelectasis but there were no statistically significant differences in pneumonia and gastric distension. Conclusion: The use of immediate CPAP after sleeve gastrectomy in morbidly obese patients is effective in improving oxygenation, spirometric values, reducing atelectasis and decreasing postoperative pulmonary complications.